2018
DOI: 10.1002/lt.25013
|View full text |Cite
|
Sign up to set email alerts
|

Heparin but not tissue plasminogen activator improves outcomes in donation after circulatory death liver transplantation in a porcine model

Abstract: Ischemic-type biliary lesions (ITBLs) arise most frequently after donation after circulatory death (DCD) liver transplantation and result in high morbidity and graft loss. Many DCD grafts are discarded out of fear for this complication. In theory, microvascular thrombi deposited during donor warm ischemia might be implicated in ITBL pathogenesis. Herein, we aim to evaluate the effects of the administration of either heparin or the fibrinolytic drug tissue plasminogen activator (TPA) as means to improve DCD liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 54 publications
(102 reference statements)
1
20
0
Order By: Relevance
“…We showed that our bioengineered hepatic tissue was ectopically expanded more than 400‐fold and self‐organized into vascularized liver structures that were actively functional. Moreover heparin has been shown to inhibit immune cell infiltration and prolong graft survival . In our study, we also showed that heparin offered anti‐inflammatory capacity (less immune cell infiltration) and conferred a cytoprotective effect (fewer apoptotic cells) to help the bioengineered hepatic tissue survive.…”
Section: Discussionsupporting
confidence: 68%
“…We showed that our bioengineered hepatic tissue was ectopically expanded more than 400‐fold and self‐organized into vascularized liver structures that were actively functional. Moreover heparin has been shown to inhibit immune cell infiltration and prolong graft survival . In our study, we also showed that heparin offered anti‐inflammatory capacity (less immune cell infiltration) and conferred a cytoprotective effect (fewer apoptotic cells) to help the bioengineered hepatic tissue survive.…”
Section: Discussionsupporting
confidence: 68%
“…Interventions include, for example, the use of thrombolytics in the donor or recipient, normothermic perfusion after procurement, and use of extracorporeal membrane oxygenation after cardiac arrest . Additional modifiable recipient risk factors include the following: Hepatectomy time. Recipient WIT. CIT. …”
Section: Discussionmentioning
confidence: 99%
“…(8,9,24) The modifiable donor risk factors are as follows: Interventions include, for example, the use of thrombolytics in the donor or recipient, normothermic perfusion after procurement, and use of extracorporeal membrane oxygenation after cardiac arrest. (8,9,13,(25)(26)(27)(28)(29) Additional modifiable recipient risk factors include the following (30)(31)(32) :…”
Section: Expanding the Dcd Donor Poolmentioning
confidence: 99%
“…Our previous work has shown that routine use of tPA in the setting of DCD transplant may be one cost‐effective strategy for prevention of NAS in this particularly susceptible population . Recently, however, other studies have called into question the role of microthrombi in biliary stricture development after DCD transplantation as well as the utility of tPA in reducing biliary stricture incidence DCD liver transplant recipients, pointing toward the need for a multi‐institution, randomized trial to more clearly assess the value of routine tPA use in DCD transplantation for prevention of biliary strictures …”
Section: Discussionmentioning
confidence: 99%